Pelatihan Pemanfaatan Media Sosial untuk Memberdayakan Warga dalam Memanfaatkan Peluang Berwirausaha di Kelurahan RT 01/RW 08, Tegal Gundil , Kota Bogor: Pengabdian - Fujiyati; Cucu Sumartini, Lilis; Nisaa, Istiqoomatun; Wisnu Nugroho, Haris (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Information technology is currently developing very rapidly. These developments affect our way of life and daily activities. With the increasing use of the internet, people can access almost all the information they need easily and quickly. Many people use various social media platforms to interact and communicate with others, whether for business purposes, sharing daily activities, or socializing online. Apart from being a communication tool, social media also has a business function. This training was held to provide an understanding to the trainees that entrepreneurial opportunities can be found through social media, especially Instagram and WhatsApp, if these social media platforms are widely used and active in the participants' daily lives. This training was carried out by the lecture method with participants from RT 01/RW 08 Tegal Gundil Village. North Bogor District, Bogor City. This training aims to create new awareness so that participants can apply the training materials in their daily lives.